Correlation of NLR and D-dimer Levels with Clinical Severity of COVID-19 and Determination of Cut-off Values at a Hospital in Cirebon - Sari, Fitria Ratna; Nilapsari, Rika (Global Medical & Health Communication (GMHC), 2024)
Inflammation and coagulation markers play a crucial role in assessing the systemic involvement of COVID-19. Early identification of disease severity through neutrophil-lymphocyte ratio (NLR) and D-dimer levels can aid physicians in promptly identifying potentially severe cases and determining appropriate treatment strategies. This study explored the relationship between NLR, D-dimer levels, and clinical severity in COVID-19 patients. This retrospective cross-sectional study reviewed 237 medical records of adult COVID-19 patients treated at Permata Cirebon Hospital from July to October 2021. The seriousness of COVID-19 served as the outcome variable, while NLR and D-dimer values were considered independent variables. Correlation analysis examined the relationship between NLR, D-dimer, and COVID-19 severity. Receiver operating characteristic (ROC) curve analysis was employed to establish the cut-off values. The majority of COVID-19 patients exhibited moderate disease severity. Male gender, advanced age, and comorbidities such as diabetes, hypertension, CVD, and stroke were associated with a higher likelihood of severe disease. A significant positive correlation was found between NLR and disease severity, as well as between D-dimer and disease severity. Notably, the correlation between D-dimer and disease severity was more substantial than that of NLR. Furthermore, the cut-off values obtained from the ROC analysis were 3.79 for NLR (sensitivity=68.8%, specificity=68.1%) and 1,110 for D-dimer (sensitivity=79.2%, specificity=87.5%). The study revealed a significant positive correlation between the severity of NLR, D-dimer levels, and COVID-19. Therefore, NLR and D-dimer can serve as prognostic markers for COVID-19 patients.